Difficulties in Diagnosing Isolated IgG4-associated Sclerosing Cholangitis - Zsóri, Gábor; Illés, Dóra; Tiszlavicz, László; Czakó, László (Journal of Digestive Endoscopy, 2019)
The most common causes of recurrent cholangitis are biliary stones and neoplasia. Primary types of sclerosing cholangitis such as IgG4-associated sclerosing cholangitis (IgG4-SC) and primary sclerosing cholangitis (PSC) are rare causes of recurrent cholangitis. Differentiating diagnoses for IgG4-SC and PSC is essential because of the significant difference in treatment. We report a challenging case of recurrent cholangitis.
Keywords: IgG4-associated sclerosing cholangitis; primary sclerosing cholangitis; recurrent cholangitis